2010
DOI: 10.1167/10.12.14
|View full text |Cite
|
Sign up to set email alerts
|

I can see you better if I can hear you coming: Action-consistent sounds facilitate the visual detection of human gait

Abstract: Observers are remarkably sensitive to point-light displays of human movement. The Superior Temporal Sulcus (STS) and premotor cortex are implicated in the visual perception of point-light human actions and the integration of perceptual signals across modalities. These neurophysiological findings suggest that auditory information might impact visual sensitivity to point-light displays of human actions. Previous research has demonstrated that coincident, action-consistent sounds enhance visual sensitivity to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 59 publications
(71 reference statements)
3
35
0
Order By: Relevance
“…Yet, perception in a complex sports situation never relies on only one sense. For instance, other studies have analyzed the relation between the auditory and visual senses (Thomas & Shiffrar, 2010;Sevdalis & Keller, 2010). This was examined by presenting point-light displays with added auditory information.…”
mentioning
confidence: 99%
“…Yet, perception in a complex sports situation never relies on only one sense. For instance, other studies have analyzed the relation between the auditory and visual senses (Thomas & Shiffrar, 2010;Sevdalis & Keller, 2010). This was examined by presenting point-light displays with added auditory information.…”
mentioning
confidence: 99%
“…This linear walking motion was subsequently rendered into point-light movies. The construction of the pointlight movies is described in extensive detail elsewhere (Thomas & Shiffrar, 2010).…”
Section: Stimulimentioning
confidence: 99%
“…For example, the sounds of female footsteps impact the perception of point-light walker gender (Van der Zwan et al, 2009), and the sounds of tap dancing enhance visual sensitivity to point-light tapping feet (Arrighi et al, 2009). Research from our own lab has shown that visual sensitivity to point-light walking is enhanced when paired with footstep sounds, but not when paired with temporally synchronous but meaningfully unrelated control sounds (Thomas & Shiffrar, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…integration, motor perception, and motor learning (CalvoMerino, Ehrenberg, Leung, & Haggard, 2010;Elsner, FalckYtter, & Gredebäck, 2012;Graf et al, 2007;Hodges, Hayes, Breslin, & Williams, 2005;Petrini, Holt, & Pollick, 2010;Springer, Brandstadter, & Prinz, 2013;Stadler, Springer, Parkinson, & Prinz, 2012;Thomas & Shiffrar, 2010). Furthermore, they have been applied to investigate the brain processing underlying the visual and motor properties of actions, by means of functional magnetic resonance imaging (Beauchamp, Lee, Haxby, & Martin, 2003;Grossman et al, 2000;Saygin, Wilson, Hagler, Bates, & Sereno, 2004), electroencephalography (Hirai, Watanabe, Honda, & Kakigi, 2009;Krakowski et al, 2011;Ulloa & Pineda, 2007), and transcranial magnetic stimulation (Grossman, Battelli, & Pascual-Leone, 2005;van Kemenade, Muggleton, Walsh, & Saygin, 2012).…”
mentioning
confidence: 99%